Effects of three types of thought content instructions on skiing performance - Rushall, B. S.; Hall, M.; Roux, L.; Sasseville, J.; Rushall, A. C (The Sport Psychologist, 1988)
Canadian National and Olympic Cross-country Ski Team members (N = 18) were instructed to plan and use positive self-talk while performing training loop repetitions at a steady pace. S's were instructed to concentrate on positive self-talk for the duration of a loop, which ranged between 70 and 100 sec depending upon the S. On alternate loops, Ss were instructed to use the type of thinking they normally engaged in performing such a task ("training thinking"). All Ss, save one, improved their times for a loop by an average of -3.07%, while heart rates increased by only 1.2%. Ss were not aware of any change in effort between trials. An ANCOVA showed the performance change was significantly greater than that which could be attributed to change in effort as revealed by HRs as well as being significantly different to the training-thinking condition. This result showed that normal training thought content and patterns are not conducive to the best quality of training response. Focusing thought content on positive thinking is a way of improving training performances which may be accompanied by a minor increase in work effort that is below the awareness threshold of athletes. Implication: Training thought content of national and Olympic standard skiers is not conducive to the best training response. By emphasizing positive thought content during repetitious training sets, response quality can be improved in a consistent manner. The amount of improvement will be very noticeable.